Review of "Beyond Bultmann. Reckoning a New Testament theology." Edited by Bruce W. Longenecker and Mikeal C. Parsons. - Bockmuehl, M (Cambridge University Press, 2017)
Rudolf Bultmann’s Theology of the New Testament, which shaped generations of students during his lifetime (1886-1976) and beyond, is here revisited by a stellar cast of contributors, eleven of whom each address one of its chapters while two others provide synthetic conclusions.